2006
DOI: 10.1021/jp056577q
|View full text |Cite
|
Sign up to set email alerts
|

Excited States of Weakly Bound Bosonic Clusters:  Discrete Variable Representation and Quantum Monte Carlo

Abstract: We compare two approaches for the accurate calculation of the energy levels of weakly bound boson trimers. The first approach is based on correlation function Monte Carlo employing optimized trial functions, while the second approach is based on the discrete variable representation. A trimer with atoms of half the mass of neon is used as a test problem for benchmark calculations. The two approaches yield identical results, within error bars, for all the J = 0 energy levels below the dissociation threshold. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…There have been extensive theoretical studies of the bound state energy levels and structures of weakly bound bosonic van der Waals trimers for J = 0 in the literature during the past two decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Rovibrational calculations have been carried out only recently for Ne 3 by Salci et al, 18 and for Ar 3 by Márquez-Mijares et al 19 and Karlický et al, 20 while He 3 has been found to support no J > 0 bound state. 21 In the present work, we study theoretically the bosonic rare gas van der Waals trimer Ne 3 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been extensive theoretical studies of the bound state energy levels and structures of weakly bound bosonic van der Waals trimers for J = 0 in the literature during the past two decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Rovibrational calculations have been carried out only recently for Ne 3 by Salci et al, 18 and for Ar 3 by Márquez-Mijares et al 19 and Karlický et al, 20 while He 3 has been found to support no J > 0 bound state. 21 In the present work, we study theoretically the bosonic rare gas van der Waals trimer Ne 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, variational ͑VMC͒ and DMC are much simpler in flat manifolds. [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] The works we have cited are applications of VMC and DMC to clusters in Cartesian coordinates, and constitute only a small sample of the most recent investigations. On the other hand, diffusion in manifolds remains a topic of research in pure mathematics as well as mathematical physics.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational shift for the trimers can also be calculated exactly and perturbatively using the Lanczos diagonalization in Pekeris coordinates. These shifts are shown in Table , along with the simulation and experimental results. For each of the isotopologues, 90 dimensionless Jacobi DVR basis functions were used over 15000 iterations with a V max of 1000 cm –1 for all cases except for the Lanczos–Exact calculation with (pH 2 ) 3 ( V max = 1100 cm –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the trimer bound state energy calculations, , performed using the Lanczos diagonalization scheme, are shown in Table using both the full pointwise H1-P and our fitted H1-MLR. We find two bound states for (pH 2 ) 3 , three for (oD 2 ) 3 , and four for (pT 2 ) 3 .…”
Section: Resultsmentioning
confidence: 99%